Feasibility and acceptability of human papillomavirus self‐sampling in a semi‐urban area in northern Tanzania. Issue 1 (6th February 2021) - Mahande, Michael J.; Oneko, Olola; Amour, Caroline; Pollie, Meridith; Smith, Cheyenne; Mboya, Innocent B.; Finkel, Madelon
Abstract: Objective: To assess the feasibility and acceptability of HPV self‐sampling in Arusha region, northern Tanzania, because the ability for women to self‐collect HPV samples can help reduce the number of health facility visits and improve cervical cancer screening coverage rates. Methods: We conducted a facility‐ and community‐based cross‐sectional study among 350 women aged 25–55 years in Arumeru district, Arusha region, northern Tanzania. Women were trained to self‐collect an HPV sample, and follow‐up visits were used to provide results after laboratory testing. Data were analyzed using Stata version 15.1 and summarized using mean and standard deviation for numeric variables and frequencies and percentages for categorical variables. Results: Among 350 women, 65 (18.6%) ever screened for cervical cancer, all provided self‐collected samples, and 349 (99.4%) would advise their female friends to undergo the same procedure. The prevalence of positive HPV results was 31 (8.9%), of which 26 (83.9%) were further examined. Two women found with lesions were treated following the national guidelines. Conclusion: This study has demonstrated that the HPV self‐sampling intervention for cervical cancer screening is a feasible and acceptable intervention, especially in resource‐limited countries like Tanzania. Scaling‐up policies should consider addressing the potential barriers to the uptake of this intervention. Synopsis: This study has demonstrated that the HPV self‐sampling intervention for cervical cancer screening is a feasible and acceptable intervention, especially in resource‐limited countries like Tanzania.